Current approaches to drug discovery for chagas disease: Methodological advances - Scarim, Cauê B. [UNESP]; Chin, Chung M. [UNESP] (Bentham Science Publishers, 2019)
Background: In recent years, there has been an improvement in the in vitro and in vivo methodology for the screening of anti-chagasic compounds. Millions of compounds can now have their activity evaluated (in large compound libraries) by means of high throughput in vitro screening assays. Objective: Current approaches to drug discovery for Chagas disease. Method: This review article examines the contribution of these methodological advances in medicinal chemistry in the last four years, focusing on Trypanosoma cruzi infection, obtained from the PubMed, Web of Science, and Scopus databases. Results: Here, we have shown that the promise is increasing each year for more lead compounds for the development of a new drug against Chagas disease. Conclusion: There is increased optimism among those working with the objective to find new drug candidates for optimal treatments against Chagas disease.
Keywords: Bioluminescence imaging; Chagas disease; Drug development; Methodological advances; New drugs; Trypanosoma cruzi